A century of strategic management and corporate sustainability: how may bank-owned projects avoid bankruptcies. (16th January 2020) - Mansour, Aly; Chakrabarty, Subhra
This study analysed sustainable corporate projects as a means of lifting consequences of financial and economic crises on affected societies, with applications pertaining to rural societies that have suffered the most in certain areas. Unemployment, for example, contributed to the rise in crime rate, divorce, drug problems, and other social problems within several societies. The study hypothesised that bank-owned projects pool may continue on its growth despite financial and economic upheavals. The methodology followed was a case study analysis of existing bank-owned projects pool of Banque Misr with over 60 sustainable projects for almost a century. The findings have presented classic bank-owned projects pool with a higher growth rate. In conclusion, the study recommended bank-owned projects pool as an alternative to face default on loan payments, corruption, bankruptcies, unemployment, poor healthcare services, and low standards of education due to the financial and economic global upheavals in recent years.